Effectiveness of Integrated Technology Apps for Supporting Healthy Food Purchasing and Consumption: A Systematic Review - Sook-Yee Lim; Kai-Wei Lee; Wen-Li Seow; Navin Kumar Devaraj; Syafinaz Amin-Nordin; Nurul Azmawati Mohamed @ Abd Aziz (MDPI Multidisciplinary Digital Publishing Institute, 2024)
Indexed by WOS/Scopus/ERA